Implementasi Metode Yanbu’a Dalam Pembelajaran Baca Tulis Al-Qur’an di MI Roudlotul Ulum - Ummah, Risalul; Nur Laila, Fitria (Institut Agama Islam Uluwiyah Mojokerto Indonesia, 2024)
In teaching the science of reading the Al-Qur’an, we use the Yanbu'a method. This method is a practical method in teaching the science of reading the Al- Qur’an. MI Roudlotul Ulum has used the Yanbu'a method to improve reading properly and correctly. This research aims to determine the implementation of the yanbu'a method in learning to read and write the Al-Qur'an (BTQ) at MI Rouldotul Ulum. The problem formulation of this research is how to implement the yanbu'a method in learning to read and write the Al-Qur'an (BTQ) at MI Roudlotul Ulum. This research uses a type of field research with a qualitative field approach. The data collection methods used by researchers are interviews, observation and documentation. Based on the results of the analysis, it can be concluded that the Al-Qur’an learning process using the Yanbu'a method has gone well according to the teaching procedures that have been determined in the Yanbu'a book on teaching guidance. The effectiveness of the yanbu'a method in learning to read and write the Al-Qur’an at MI Roudlotul Ulum can be seen from the supporting factors. The supporting factor for implementing the Yanbu'a method at MI Roudlotul Ulum is the quality or ability of educators in applying the Yanbu'a method.